Analysis Strategy Marketing In Increasing Sales During The Covid-19 Pandeml In Burger King Bandar Lampung - Sidauruk, Antonius; Habiburahman, Habiburahman (BIMA Journal (Business, Management, & Accounting Journal), 2023)
Burger King is a fast food product that generally comes from outside the country, so the taste is different from the taste of local food. Therefore, the Burger King industry is familiarizing flavors with Indonesia, such as making beef burgers with rendang flavor and serving the menu with rice. Raja Bandar Lampung. This research uses a qualitative study procedure. The information analysis uses SWOT analysis. Based on the results of studies and reviews, it can be concluded that the results of the study put the marketing strategy in quadrant I which is called the development and development strategy. The average cell for the IFE matrix and the average cell for the EFE matrix. This position allows the owner to carry out intensive strategies and integrative strategies. Intensive strategies include: market penetration by expanding the market share by marketing/promoting Burger King products, market development by expanding the market share geographically to new areas and product development by customizing Burger King products, this is usually attempted when the product is in position. he is sick and tired. In quadrant I, there are integrative strategies, namely forward integration, backward integration and horizontal integration.